Estudio de la gastronomía típica y cultura de las huecas y recetas en la zona norte de la provincia de Los Ríos, 2020 - Ferrin Romero, Dalys Leonela (2020)
The present research project includes the study of the typical gastronomy and culture of the huecas and recipes in the northern zone of the province of Los Ríos. The diagnosis of the current situation and the gastronomic characteristics of the cantons of Buena Fe, Quevedo and Valencia was made, where seventeen huecas and nineteen typical dishes were determined through personal interviews with each of the owners of the huecas culinarias (typical food restaurants), At the same time, information was collected for the data sheets of the restaurants and recipes of the northern zone, in addition a gastronomic guide was elaborated where the review of the culinary huecas, the description of the dish of its specialty, photo, name of the owner, address, map or location, social networks and recipes of the typical food were described. The gastronomic guide tries to highlight the representative dishes and their importance in the gastronomic culture of each of the Buenafecinos, Quevedeños and Valencianos. Key words: Typical food, culinary huecas, gastronomy, recipes, gastronomic guide.